Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of the Seminar on Engineering Subject Matter Expert Exchanges - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Alhamdulillah, it is indeed a great pleasure that I have the honour of welcoming you all to the Gambang Campus of University Malaysia Pahang in this auspicious occasion, that marks the commencement of the inaugural Seminar on Engineering Subject Matter Expert Exchanges (SMEE).